Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pone.0159060
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Reference Genes for Reverse Transcription Quantitative PCR Studies of Physiological Responses in the Ghost Moth, Thitarodes armoricanus (Lepidoptera, Hepialidae)

Abstract: Reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) is the sensitive method to quantify the expression levels of target genes on the basis of endogenous control. An appropriate reference gene set for normalization is essential for reliable results. The ghost moth, Thitarodes armoricanus, a host species of a medicinal fungus, Ophiocordyceps sinensis, is an economically important member of the Lepidoptera. Recent studies have focused on the mechanism of adaptation of this species to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…Various studies have already been accomplished by identifying HKGs in different species and tissues. Recently, numerous reference genes have been testified under different conditions in stinkbug (Bansal et al , 2016), western flower thrips [ 46 ], honey bee [ 47 ], fly [ 48 ], silkworm [ 49 ], moths [ 50 ] and beetles [ 51 ]. The analysis of reference genes in cotton leafhopper across different developmental stages showed variation in expression as reported in several other insects [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have already been accomplished by identifying HKGs in different species and tissues. Recently, numerous reference genes have been testified under different conditions in stinkbug (Bansal et al , 2016), western flower thrips [ 46 ], honey bee [ 47 ], fly [ 48 ], silkworm [ 49 ], moths [ 50 ] and beetles [ 51 ]. The analysis of reference genes in cotton leafhopper across different developmental stages showed variation in expression as reported in several other insects [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the expression of reference genes is not static in different species, tissues or experimental conditions (Lu et al, 2013 ), so the stability verifications of reference genes are necessary before evaluating target gene expression levels by RT-qPCR. Recently, more and more research considered this and the stability verifications were also performed in many Lepidoptera insects, for example: Plutella xylostella (Fu et al, 2013 ), Danaus plexippus (Pan et al, 2015 ), Sesamia inferens (Lu et al, 2015 ), Heliconius numata (Piron Prunier et al, 2016 ), Thitarodes armoricanus (Liu et al, 2016 ), Bombyx mori (Guo et al, 2016 ), Helicoverpa armigera (Chandra et al, 2017 ), Grapholita molesta (Wang et al, 2017 ), Chilo suppressalis (Xu et al, 2017 ), Spodoptera exigua (Płachetka-Bozek and Augustyniak, 2017 ), and grassland caterpillars (Zhang et al, 2017 ). As the important agricultural pest, the identification and validation of reference genes in S. litura with three biotic factors and four abiotic treatments were also investigated (Lu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The first RGs were brought from Northerns and usually encoded proteins involved in structural functions and basic cell metabolism due to their theoretical expression invariability in most tissues. This initial election was revealed inappropriate [ 2 4 ] and the quest of more reliable RGs has been pursued in the literature [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%